Some Features of Research Activity in the Society of Knowledge - Yudin, Boris G. (The New Research of Tuva, 2009)
In the article, the philosophical aspects of technologization of knowledge, which can cease to be innovative in the modern period and become a form of routinization of research activity, are considered.
Keywords: research activity; society of knowledge; technologization; routinization